Adipose‐ and bone marrow‐derived mesenchymal stem cells display different osteogenic differentiation patterns in 3D bioactive glass‐based scaffolds. (3rd December 2013) - Rath, Subha N.; Nooeaid, Patcharakamon; Arkudas, Andreas; Beier, Justus P.; Strobel, Leonie A.; Brandl, Andreas; Roether, Judith A.; Horch, Raymund E.; Boccaccini, Aldo R.; Kneser, Ulrich
Abstract: Mesenchymal stem cells can be isolated from a variety of different sources, each having their own peculiar merits and drawbacks. Although a number of studies have been conducted comparing these stem cells for their osteo‐differentiation ability, these are mostly done in culture plastics. We have selected stem cells from either adipose tissue (ADSCs) or bone marrow (BMSCs) and studied their differentiation ability in highly porous three‐dimensional (3D) 45S5 Bioglass®‐based scaffolds. Equal numbers of cells were seeded onto 5 × 5 × 4 mm 3 scaffolds and cultured in vitro, with or without osteo‐induction medium. After 2 and 4 weeks, the cell–scaffold constructs were analysed for cell number, cell spreading, viability, alkaline phosphatase activity and osteogenic gene expression. The scaffolds with ADSCs displayed osteo‐differentiation even without osteo‐induction medium; however, with osteo‐induction medium osteogenic differentiation was further increased. In contrast, the scaffolds with BMSCs showed no osteo‐differentiation without osteo‐induction medium; after application of osteo‐induction medium, osteo‐differentiation was confirmed, although lower than in scaffolds with ADSCs. In general, stem cells in 3D bioactive glass scaffolds differentiated better than cells in culture plastics with respect to their ALP content and osteogenic gene expression. In summary, 45S5 Bioglass‐based scaffolds seeded with ADSCs are well‐suited for possible bone tissue‐engineering applications. Induction of osteogenic differentiation appears unnecessary prior to implantation in this specific setting. Copyright © 2013 John Wiley & Sons, Ltd.